THE EFFECT OF VIDEO AS AN INSTRUCTIONAL MEDIA ON ARABIC PRONUNCIATION ABILITY: AN EXPERIMENTAL STUDY AT ISLAMIC JUNIOR HIGH SCHOOL (MTsS) BUKIT SILEH SOLOK / ØªØ£Ø«ÙŠØ± ÙˆØ³ÙŠÙ„Ø© ÙÙŠØ¯ÙŠÙˆ Ø§Ù„ØªØ¹Ù„ÙŠÙ… Ø¹Ù„Ù‰ Ù‚Ø¯Ø±Ø© Ù†Ø·Ù‚ Ø§Ù„Ø¹Ø±Ø¨ÙŠØ© : Ø¨ØØ« ØªØ¬Ø±ÙŠØ¨ÙŠ ÙÙŠ Ø§Ù„Ù…Ø¯Ø±Ø³Ø© Ø§Ù„Ø«Ø§Ù†ÙˆÙŠØ© Ø§Ù„Ø¥Ø³Ù„Ø§Ù…ÙŠØ© Ø§Ù„Ø£Ù‡Ù„ÙŠØ© Ø¨ÙˆÙƒØª Ø³ÙŠÙ„Ø© Ø³ÙˆÙ„ÙˆÙƒ - Amelia Amelia; Al Anisah; Lathifah Al Husna (IAIN Batusangkar, Indonesia, 2023)
The purpose of this study was to determine the effect of using video as an instructional media on studentsâ€™ ability to pronounce Arabic hijaiyah letters at MTsS Bukit Sileh. This research used a quasi-experimental method and test was the instrument to collect the data. The results of the study describe that there were differences in the ability ofÂ pronouncing Arabic hijaiyah letters between students who studied using video as an instructional media and those who studied without using video. The average of experimental class was 85.23, while the control class was 65.6. After calculating t test, the score of t0 was 4.48 andÂ tt was 2.08. it indicates that t0 was higher than tt (4,48 > 2,08). Therefore, H0 was rejected and Ha was accepted. It means that the use of video as an instructional video has an effect on studentsâ€™ ability in pronouncing Arabic hijaiyah letters.